Edukasi Pentingnya Membaca dan Manfaat Literasi Bagi Siswa Kelas 2 Di SDN Besowo 2 - Nikmatus soimah; Ni’matul Layla (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2022)
Books are one of the sources of knowledge that add insight. By reading a person can find out what is around the world. This makes books often referred to as windows to the world. Reading books is also an activity that has many benefits and is best applied at the earliest possible age or the age of children. But in reality not many children have a high interest in reading due to several factors. Especially like now. where the development of technology is very fast and rapid causing any information can be easily obtained through gadgets. So the activity of reading books is starting to be abandoned. The Teras Baca program aims to restore interest in reading in children, provide reading material for them and as a place for them to study. In this study, researchers used the LITERATURE method. The LITERATURE method is a strategy to shape the creativity of students through its 5 components, namely observing, asking, reasoning, trying, and communicating. Namely by directly holding a mimbel program for children. With this program, it is hoped that it can foster interest and instill reading habits in children.